Production and utilization of products from commercial seaweeds - McHugh, D.J. (Rome Food and Agriculture Organizations of the United Nations, 1987)
FAO Fish Tech. Paper; no. 288
Keywords: Seaweed products; Seaweed use; Seaweed culture; Seaweed culture--Economic aspects